2019
DOI: 10.1111/jocd.12972
|View full text |Cite
|
Sign up to set email alerts
|

Skin‐lightening practices behind the veil: An epidemiological study among Saudi women

Abstract: Background: Women are adopting skin-lightening practices worldwide in an attempt to enhance their skin tone. The reasons and beliefs behind such practices vary from culture to culture. Scarce data are available for this phenomenon among Saudi women. We carried out this study to determine the practices, reasons, and correlates of skin-lightening practices among women in the northern region of Saudi Arabia. Method: Using nonprobability convenient sampling, an analytical cross-sectional study was carried out amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
23
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 18 publications
5
23
2
Order By: Relevance
“…In addition, the proportion of SLP users among bachelor graduates was significantly higher than among nonusers in relation to educational level (69.2% vs. 54.0%, p = 0.009). Consistent with the present results, previous studies have shown a significant difference in education level; out of a total of 375 collegeeducated participants, 65.7% were skin whitening users, comparable to a total of 230 students using 34.3% skin whitening users [6].…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the proportion of SLP users among bachelor graduates was significantly higher than among nonusers in relation to educational level (69.2% vs. 54.0%, p = 0.009). Consistent with the present results, previous studies have shown a significant difference in education level; out of a total of 375 collegeeducated participants, 65.7% were skin whitening users, comparable to a total of 230 students using 34.3% skin whitening users [6].…”
Section: Discussionsupporting
confidence: 92%
“…Using skin-lightening products has become highly prevalent among the general population worldwide [4]. In Saudi Arabia, it has shown a prevalence of 56.2% [5].Among many skin lightening techniques, Kligman's formula is one of the first chosen options, reflecting widespread usage.…”
Section: Introductionmentioning
confidence: 99%
“…In Saudi Arabia, it has shown a prevalence of 56.2% [5].Among many skin lightening techniques, Kligman's formula is one of the first chosen options, reflecting widespread usage. Other indications of Kligman's formula include dyspigmentation, getting rid of scars, and skin peeling/exfoliation [4,5]. Kligman's formula has been associated with many adverse events (AEs).…”
Section: Introductionmentioning
confidence: 99%
“…Skin lightening practices have escalated worldwide in an attempt to enhance skin tone. A study conducted in the Northern Region of Saudi Arabia by Alrayyes, Alrayyes, & Farooq Dar (2020) highlights the increasing use of skin lightening products. Various reasons and beliefs were found behind these practices.…”
Section: Discussionmentioning
confidence: 99%